Band Alignment and Optical Properties of (ZrO2)0.66(HfO2)0.34 Gate Dielectrics Thin Films on p-Si (100) - Dahlang Tahir; Hee Jae Kang; Sven Tougaard (Institute for Research and Community Services (LPPM) ITB, 2011)
(ZrO2)0.66(HfO2)0.34 dielectric films on p-Si (100) were grown by atomic layer deposition method, for which the conduction band offsets, valence band offsets and band gaps were obtained by using X-ray photoelectron spectroscopy and reflection electron energy loss spectroscopy. The band gap, valence and conduction band offset values for (ZrO2)0.66(HfO2)0.34 dielectric thin film, grown on Si substrate were about 5.34, 2.35 and 1.87 eV respectively. This band alignment was similar to that of ZrO2. In addition, the dielectric function ï¥(k, Ï‰), index of refraction n and the extinction coefficient k for the (ZrO2)0.66(HfO2)0.34 thin films were obtained from a quantitative analysis of REELS data by comparison to detailed dielectric response model calculations using the QUEELS-Îµ (k,Ï‰)-REELS software package. These optical properties are similar with ZrO2 dielectric thin films.